FREUDIAN NARCISSISM IN CROSS-MEDIA STORYTELLING: The Curious Case of Nujeen Mustafa. - Sousa, Rodrigo Almeida (Politeia, 2020)
The importance of storytelling in the 21st Century’s media is indisputable. Facts alone do not satisfy our desire for identity. Only stories can provide us with a sense of identification and belonging. However, stories can also exacerbate our emotional and narcissistic response; and this is precisely what post-truth storytelling is all about: fact-devaluation, appeal to the emotions, extreme partiality and aggressive rhetoric. Based on Freud's theory of narcissism, our research article proposes an objective and interdisciplinary model from which we can recognise, depict and analyse narcissistic patterns in today’s cross-media storytelling. In effect, this will help us to better understand the story of the refugee Nujeen Mustafa, which seems to illustrate so well our explicit and implicit dynamics of self-love.
Keywords: Post-truth; Aggressiveness; Prejudice; Idealisation; Migrants; Refugees